2019
DOI: 10.18632/aging.102265
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MALAT1 promotes cardiac remodeling in hypertensive rats by inhibiting the transcription of MyoD

Abstract: Hypertension is the leading preventable cause of premature deaths worldwide. Although long non-coding RNA (lncRNA) metastasis associated lung adenocarcinoma transcript 1 (MALAT1) has been identified to play important roles in the development of cardiovascular diseases, the regulatory function of lncRNA MALAT1 in hypertension remains poorly understood. This study aimed to explore the role of lncRNA MALAT1 in spontaneously hypertensive rats (SHRs). LncRNA MALAT1 was determined to be elevated and MyoD to be reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…However, the results are not optimistic due to the complicated pathology of hypertension [34]. Vascular remodeling is a process of vascular structural changes that involves several cellular processes, including cell proliferation, migration, inflammation, and apoptosis [26, 35]. Physiological remodeling occurs as an adaptive response to hemodynamic and age-related changes [36, 37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the results are not optimistic due to the complicated pathology of hypertension [34]. Vascular remodeling is a process of vascular structural changes that involves several cellular processes, including cell proliferation, migration, inflammation, and apoptosis [26, 35]. Physiological remodeling occurs as an adaptive response to hemodynamic and age-related changes [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…First, 150 mg/kg pentobarbital sodium was intraperitoneally injected into 5 SHRs to euthanize the SHRs on an aseptic operating table as described previously [26]. Subsequently, the cardiopulmonary tissues were rapidly resected and preserved in aseptic Hanks solution containing penicillin-streptomycin (15140-122, Gibco, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of MALAT1 expression rescued the rats’ cardiac function due to a restoration of the PI3K/AKT signaling pathway [ 148 ]. Studies in the rat model of hypertension showed that MALAT1 expression was increased in the heart [ 149 , 150 ]. Overexpression of MALAT1 caused severe cardiac fibrosis and remodeling by reducing the expression of MyoD that is responsible for the contractile phenotype of the heart [ 149 ].…”
Section: Long Non-coding Rnas In Cvdmentioning
confidence: 99%
“…Studies in the rat model of hypertension showed that MALAT1 expression was increased in the heart [ 149 , 150 ]. Overexpression of MALAT1 caused severe cardiac fibrosis and remodeling by reducing the expression of MyoD that is responsible for the contractile phenotype of the heart [ 149 ]. MALAT1 recruits the Suv39h1, a histone methyltransferase enzyme, to MyoD loci and causes H3K9me3 trimethylation to silence MyoD expression [ 149 ].…”
Section: Long Non-coding Rnas In Cvdmentioning
confidence: 99%